2018
DOI: 10.1007/s10029-018-1811-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of polypropylene mesh in contaminated and dirty strangulated hernias: short-term results

Abstract: The use of polypropylene mesh for contaminated and dirty strangulated hernias is effective and safe, with acceptable morbidity and good short-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
24
1
2
Order By: Relevance
“…However, depending on the localization and fixation of the previous mesh, the problem could range from an asymptomatic patient to a patient with a solid mass and pain. Regarding mesh removal, most of the studies concern the removal of infected mesh [7][8][9][10][11][12]. Although some studies concern laparoscopic repair of recurrent ventral hernias, there is still a lack of data about mesh removal during the procedure [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the localization and fixation of the previous mesh, the problem could range from an asymptomatic patient to a patient with a solid mass and pain. Regarding mesh removal, most of the studies concern the removal of infected mesh [7][8][9][10][11][12]. Although some studies concern laparoscopic repair of recurrent ventral hernias, there is still a lack of data about mesh removal during the procedure [13].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of mesh removal during laparoscopic repair of recurrent ventral hernias on the long-term outcome foreign body has not been comprehensively studied in the literature. Considering the removal of mesh, most of the studies concern mesh infections [ [7][8][9][10][11][12]. Data on the efficacy of mesh removal during laparoscopic repair remain missing.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional tissue herniorrhaphy resulted in a high recurrence rate, and the requirement of additional repairing operation undoubtedly increased medical costs and frustrated patients. Recent studies have shown that it is safe and effective to use a prosthetic mesh in the emergency repair of incarcerated or strangulated hernia [ 1 , 10 , 28 , 29 ]. Besides, it is recognized that intestinal necrosis and enterectomy are not absolute contraindications of performing a mesh repair [ 1 , 2 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nonabsorbable synthetic large-pore mesh does not promote infection because pores >70 μm allow the white blood cells and macrophages to reach the bacteria, which are often <1 μm. 9 …”
Section: Discussionmentioning
confidence: 99%